Health‐related quality of life at 3 months following head and neck cancer treatment is a key predictor of longer‐term outcome and of benefit from using the patient concerns inventory. (17th February 2022) - Kanatas, Anastasios; Lowe, Derek; Rogers, Simon N.
Abstract: Introduction: During clinical follow‐up it can be difficult to identify those head and neck cancer (HNC) patients who are coping poorly and could benefit from additional support. Health‐related quality of life (HRQOL) questionnaires and prompt lists provide a means by which patients can express their perceived outcomes and raise concerns. The first aim of this secondary analysis following a randomized trial was to explore which patient characteristics, at around 3 months following treatment completion (baseline), best predict HRQOL 12 months later. The second aim was to attempt to ascertain which patients were most likely to benefit from using prompt list. Methods: Cluster‐controlled pragmatic trial data were analyzed. HRQOL was measured by the University of Washington Quality of life questionnaire (UW‐QOLv4). The prompt list was the Patient Concerns Inventory (PCI‐HN). Results: The trial involved 15 eligible consultants and a median (inter‐quartile range) of 16 (13–26) primary HNC patients per consultant, with 140 PCI patients and 148 controls. Baseline HRQOL was the dominant predictor of 12‐month HRQOL with other predictors related to social, financial, and lifestyle characteristics as well as clinical stage and treatment. Although formal statistical tests for interaction were non‐significant the trend in analyses over a range of outcomes suggested that patients with worse baseline HRQOL could benefit more from the PCI‐HN. Discussion: HRQOL early post‐treatment is a key predictor of longer‐term outcome. Measuring and using HRQOL and the PCI‐HN are not only surrogates for predicting HRQOL at 15 months post‐treatment, but also tools to help guide interventions. Abstract : Health‐related quality of life (HRQOL) early post‐treatment is a key predictor of longer‐term outcome. Measuring and using HRQOL and the PCI‐HN are not only surrogates for predicting HRQOL at 15 months post‐treatment, but also tools to help guide interventions.